Operationalizing the ecosystems approach: Assessing the environmental impact of major infrastructure development. (July 2017) - Zawadzka, Joanna E.; Corstanje, Ron; Fookes, Jacqueline; Nichols, Jonathan; Harris, Jim
Highlights: The impact of green infrastructure associated with a planned road on ecosystem services is quantified. Simple indices to spatially assess changes in ecosystem services are computed. Magnitude and direction of change depend on the temporal scale considered. Consideration of initial land use can help optimize future land use choices. Abstract: The ecosystem services approach is increasingly applied in the context of environmental resources management and impact assessment. Assessments often involve analysis of alternative scenarios for which potential changes in ecosystem services are quantified. For such assessments to be effective there is a requirement to represent changes in ecosystem services supply in a clear and informative manner. Here we compute Ecosystem Services Ratio (ESR), a simple index that quantifies the relative change in ecosystem service provision under altered conditions given the baseline, and the Modified Ecosystem Services State Index, which averages the ESR scores obtained for each ecosystem service assessed, to provide an overall measure of the change. Given that modelling approaches to quantification of ecosystem services often result in production of maps of ecosystem supply, the proposed metrics can be visualized as maps in support to decision making processes. We use these indices to investigate potential changes in the supply of seven modelled ecosystem services resulting from the introduction of a major road development – a highway with associated green infrastructure – into a predominantly agricultural landscape in the UK. We find that the planted woodland, scrubland and grassland can increase the supply of multiple ecosystem services not accounted for in previous green infrastructure studies, although the magnitude of change differs with the type of vegetation, initial conditions and timeframes of the assessment.